2022
DOI: 10.1209/0295-5075/ac7165
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity between success probability and coherence in Grover search algorithm

Abstract: Coherence plays a very important role in Grover search algorithm (GSA). In this paper, we define the normalization coherence , where C is a coherence measurement. By virtue of the constraint of large N and Shannon's maximum entropy principle, a surprising complementary relationship between the coherence and the success probability of GSA is obtained. Namely, , where C is in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The local diffusion operator also has the advantage of reducing circuit errors. It is also interesting to explore how the local diffusion operator influences the coherence and the success probability [49]. We leave those questions for future study.…”
Section: Benchmark Resultsmentioning
confidence: 99%
“…The local diffusion operator also has the advantage of reducing circuit errors. It is also interesting to explore how the local diffusion operator influences the coherence and the success probability [49]. We leave those questions for future study.…”
Section: Benchmark Resultsmentioning
confidence: 99%
“…x k ( )  and r k z ( ) cos2 q k when t N.  Following the idea in [72], we define the normalized a C as…”
Section: Complementarity Relations Between Tsallis Relative α Entropy...mentioning
confidence: 99%
“…Likewise, similar methods have been applied to other algorithms, including the Deutsch-Jozsa algorithm and Shor's algorithm [70], and it is found that coherence depletion always exists [70,71]. Pan, Situ and Zheng [72] have displayed the complementarity relation between coherence and the success probability in GSA via the l 1 norm of coherence. Coherence determines the performance of Shor's algorithm by bounding the success probability from below and above [73].…”
Section: Introductionmentioning
confidence: 98%
“…Formalized in terms of a quantum resource theory [3][4][5][6][7][8] the equivalence between coherence and entanglement (the fuel behind applications such as quantum dense coding [9], unhackable cryptography [10] and teleportation [11]) was recognized early on [12][13][14]. Recently, the role of coherence and its depletion during the execution of quantum algorithms has received increasing attention [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%